Epistemologi dan Ontologi Pendidikan Islam - Maturidi Maturidi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2020)
The education crisis, especially Islamic education, will greatly affect social policies or behaviour, it requires us to continue to develop education, especially in the field of Islamic education. Education, in general, is within the scope of roles, functions and goals that are not different. All aim to uphold human dignity as well as the goals of Islamic education. This study aims to determine the objectives of Islamic education, epistemology and ontology of Islamic education. This research is a type of library research, which is a research activity carried out by collecting data from various types of literature from the library. So, in this study, the author will collect data from various literature from books, journal articles and other types of work related to the subject matter of this article. The results showed that Islamic education aims to manifest Islamic values in the human person that Muslim educators strive for through a process that results in a student with a Muslim personality, faith, piety, and knowledge so that they can develop themselves into obedient servants of Allah.